2019
DOI: 10.1063/1.5110682
|View full text |Cite
|
Sign up to set email alerts
|

Exact and approximate symmetry projectors for the electronic structure problem on a quantum computer

Abstract: Solving the electronic structure problem on a universal-gate quantum computer within the variational quantum eigensolver (VQE) methodology requires constraining the search procedure to a subspace defined by relevant physical symmetries. Ignoring symmetries results in convergence to the lowest eigenstate of the Fock space for the second quantized electronic Hamiltonian. Moreover, this eigenstate can be symmetry broken due to limitations of the wavefunction ansatz. To address this VQE problem, we introduce and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…We also checked the error from the choice of mapping (Jordan-Wigner, Parity, and Bravyi-Kitaev schemes), and found that too to be well within 0.1 mH. This is not too surprising, as the transformed qubit Hamiltonians from each of these mappings are expected to be isospectral to the electronic Hamiltonian [34].…”
Section: The Effect Of the Number Of Vqe Iterations: State Preparatio...mentioning
confidence: 80%
“…We also checked the error from the choice of mapping (Jordan-Wigner, Parity, and Bravyi-Kitaev schemes), and found that too to be well within 0.1 mH. This is not too surprising, as the transformed qubit Hamiltonians from each of these mappings are expected to be isospectral to the electronic Hamiltonian [34].…”
Section: The Effect Of the Number Of Vqe Iterations: State Preparatio...mentioning
confidence: 80%
“…For all these reasons, VQE tends to be impractical for perfectly robust ansatz, and much of the literature focuses on methods for constructing effective ansatz accounting for system symmetries and hardware limitations. 15,[22][23][24][25] Because circuit depth and gate count are kept low, VQE is well-suited to NISQ devices.…”
Section: Quantum Phase Estimationmentioning
confidence: 99%
“…. ., which results in an exponential increase in the number of Pauli operators [19], hindering its practical usage.…”
Section: Vqe Algorithmmentioning
confidence: 99%
“…Thus such spin-adapted (SA) methods [16,17] still incur Trotterization for large t ab i j . Some of the previous studies on this matter have suggested the use of a constrained approach [14,[18][19][20], wherein the Hamiltonian is augmented with a penalty term λ(Ŝ 2…”
Section: Introductionmentioning
confidence: 99%